Attitude and Orbit Optimal Control of Combined Spacecraft via a Fully-Actuated System Approach - Duan, Guangquan; Liu, Guo-Ping (Journal of systems science and complexity, 2022)
This paper investigates the attitude and orbit control for the combined spacecraft formed after a target spacecraft without the autonomous control ability is captured by a service spacecraft. The optimal controller of fully-actuated system is proposed to realize the attitude and orbit stabilization control of combined spacecraft. The stability of the system is proved by introducing Lyapunov function. Numerical simulation of the combined spacecraft and physical experiment based on the combined spacecraft simulator (CSS) are completed. Both simulation and experiment results demonstrate the effectiveness and practicability of the optimal controller of fully-actuated system.